2013
DOI: 10.1088/1367-2630/15/8/083014
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of nitrogen vacancy centres in nanodiamonds by means of phonons

Abstract: Realising controlled quantum dynamics via the magnetic interactions between colour centers in diamond remains a challenge despite recent demonstrations for nanometer separated pairs. Here we propose to use the intrinsic acoustical phonons in diamond as a data bus for accomplishing this task. We show that for nanodiamonds the electron-phonon coupling can take significant values that together with mode frequencies in the THz range, can serve as a resource for conditional gate operations.Based on these results we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
79
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 56 publications
(113 reference statements)
0
79
0
Order By: Relevance
“…4 It has been demonstrated that the NV electronic spin can be entangled with and via optical photons, 5,6 and significant effort has been devoted to fabricating nanophotonic structures to create enhanced NV-photon interfaces [7][8][9][10] for efficient quantum information processing and quantum communication. In parallel, diamond nanostructures can be fabricated with very high mechanical quality factors, 11,12 and it has been proposed theoretically to exploit the coupling of NV centers to phonons, in addition to photons, for quantum information processing [13][14][15] or quantum enhanced magnetometry 16 applications. It is well known that many electronic defects in solids, including NV centers, are highly susceptible to deformations of the surrounding lattice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 It has been demonstrated that the NV electronic spin can be entangled with and via optical photons, 5,6 and significant effort has been devoted to fabricating nanophotonic structures to create enhanced NV-photon interfaces [7][8][9][10] for efficient quantum information processing and quantum communication. In parallel, diamond nanostructures can be fabricated with very high mechanical quality factors, 11,12 and it has been proposed theoretically to exploit the coupling of NV centers to phonons, in addition to photons, for quantum information processing [13][14][15] or quantum enhanced magnetometry 16 applications. It is well known that many electronic defects in solids, including NV centers, are highly susceptible to deformations of the surrounding lattice.…”
mentioning
confidence: 99%
“…Recently, there has been significant interest in exploiting these defect-phonon interactions in nanomechanical systems or phonon cavities, where single defects may be strongly coupled to long-lived, spectrally isolated phonon modes. [14][15][16][17][18][19][20][21][22] This suggests a route toward cavity quantum electrodynamics using phonons, with applications ranging from measurement and manipulation of single mechanical quanta, to the generation of single-phonon nonlinearities and phonon-meditated coupling of defects. In view of recent advances in diamond nanofabrication and demonstrated optical control of NV centers, diamond is a leading candidate material in which to pursue these directions in experiments.…”
mentioning
confidence: 99%
“…Besides its application in signal transduction and precision measurement, the proposed hybrid system can be exploited to couple the NV-center spin to mechanical oscillations, and significantly enhance the coherent coupling between these two degrees of freedom. This would allow fast mechanical control of spin qubits, large phonon induced spin-spin interaction, and efficient phonon cooling by an NV center [21][22][23][24][25][26].…”
mentioning
confidence: 99%
“…It may also find applications in spin and mechanical oscillator hybrid systems. A hybrid diamondpiezomagnetic (film) mechanical nanoresonator can significantly enhance the coupling between its vibrational mode and NV electronic spins in diamond [23,24], and thereby boost the phonon-mediated effective spin-spin interactions. This would facilitate the spin squeezing at room temperature, which can be used a resource for magnetometry and phonon-mediated quantum information processing.…”
mentioning
confidence: 99%
“…The physical origin of collective dephasing is left unspecified in the theoretical treatment here. Note that it can, for instance, arise via correlated magnetic field fluctuations for ions [28] or due to interactions with phononic baths in the case of colour centers [23,36,37] (see [38] for additional details regarding such situations).…”
mentioning
confidence: 99%